Copepod distribution in surface waters of the drake passage using continuous plankton recorder and a Pump-Net onboard system - Thompson, Gustavo Ariel; Dinofrio, Estela O.; Alder, Viviana Andrea; Takahashi, Kunio T.; Hosie, Graham W. (Brazilian Journal of Oceanography)
There is no single instrument that can sample quantitatively the complete spectrum of pelagic organisms, or even all the components of zooplankton. Mesh size is the main factor affecting species selectivity in the Continuous Plankton Recorder (CPR), implying a need to use multiple net systems to fully characterize a community. The spatial distribution of copepod communities in the water masses of the western and eastern sectors of Drake Passage were studied using, respectively, a CPR and a Pump Net onboard system. For this purpose, and assuming that copepod community size structures of each of the three water masses were similar in both the sectors studied, the possibility of complementing CPR results using a Pump-Net onboard system was evaluated. The latter system allows the estimation of absolute abundances and has the advantage of solving two problems associated with CPR, namely mesh clogging and low catching efficiency. The contribution of the nauplius forms and species accurately identified with both samplers was analyzed. Although Oithona similis dominated both communities, in the western sector small species made a greater contribution than Calanus simillimus, the opposite being true for the eastern sector. Nauplii and early copepodite stages of O. similis were missing from the CPR samples and represented between 69 and 79% of total copepod communities, whereas small calanoid copepods, C. simillimus copepodites and later stages of O. similis were inaccurately sampled by the CPR and represented between 14 and 18% of the copepod community. Hence, the Pump Net sampler is useful for complementing the semi-quantitative information of the CPR and for its calibration. Fil: Thompson, Gustavo Ariel. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología, Genética y Evolución; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Dinofrio, Estela O. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del ...